A Brief Analysis of the Changes of Female Images between China and South Africa - Hou, Junling (IJRDO - Journal of Social Science and Humanities Research, 2017)
After the Fourth World Conference on Women, ‘Media and Women’ became a significant issue in the academic research. Platform of Action made requirements about the development of media, especially focusing on the female news and images. Breaking the singular stereotypes of female images became an urgent topic. After selecting two representative newspapers and collecting all the female related news from China and South Africa respectively, we can conclude similarities and differences between the two countries. The first six months in 1995 and 2015 was the period, we could find changes on propaganda of female. Furthermore, according to the different backgrounds between two countries, analyzing reasons of changes.